2008 7th International Pipeline Conference, Volume 3 2008
DOI: 10.1115/ipc2008-64352
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of In-Service Welding Procedure Flow Restrictions

Abstract: Edison Welding Institute (EWI) and Enterprise Products Operating LP (Enterprise) worked together to develop an in-service welding program. The objective of this project was to relax flow restrictions on current in-service welding procedures to allow for welding onto liquid pipelines with flow rates outside of current flow limits. Enterprise’s current products include liquid propane, liquid ethane, and propane and ethane mixes in addition to other refined products. The current Enterprise in-service welding proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Boring et al [ 26 ] evaluated the burn-through risk based on their test device. They concluded that excessive inner diameter (ID) surface bulging, the carburized and eutectic iron layer on the ID surface, were the precursor of burn-throug instability.…”
Section: Introductionmentioning
confidence: 99%
“…Boring et al [ 26 ] evaluated the burn-through risk based on their test device. They concluded that excessive inner diameter (ID) surface bulging, the carburized and eutectic iron layer on the ID surface, were the precursor of burn-throug instability.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the consideration of engineering value, previous studies mainly focus on the evaluation criteria of in-service welding. The previous criteria mainly include the minimum wall thickness criterion [3], inner wall maximum temperature criterion [4,5], residual strength criterion and plastic failure criterion [6]. It can be found that all the failure models are based on the phenomenon and mechanism of in-service welding failure instability, but there is still a lack of research on the plastic deformation and failure mechanism of burn-through instability.…”
Section: Introductionmentioning
confidence: 99%